Studying the Effect of Laser Pump Pulse Energy and Delay Time on Conversion Efficiency of KTP - Jamal, Raied K.; Rustum, Russul Khalil (Iraqi Journal of Science, 2020)
In this study, the effect of increasing pump pulse energy and delay time on the energy conversion efficiency of the Potassium Titanyl Phosphate (KTP) crystal at room temperature was investigated. It was found that the higher the pump pulse the greater the efficiency at a certain value of the delay time. Moreover, at the delay time 3.524ns, we found that the efficiency of the conversion of energy increases from 0.0112 to 0.0159. We also observed that the lower delay time between the pump and the probe pulses leads to increase the rate of energy conversion efficiency of the KTP crystal, where the reaches up to 3, which is higher than the value recorded in the absence of a pump pulse. The highest value of the rate of energy conversion efficiency recorded in this study was 0.0159. This work was achieved at room temperature.